Digital Marketing Analysis, Lenovo Thinkpad Product Quality And Brand Image On Purchase Interest At Lasitech Computer Store - Kristin Polina Putri Damayanti Silalahi; Harianto Harianto; Firman Ario (Jurnal Fokus Manajemen, 2026)
This study aims to analyze the influence of Digital Marketing, Product Quality, and Brand Image on Consumer Buying Interest of Lenovo ThinkPad products at Lasitech Computer Stores. This study uses a quantitative approach with a survey method of 96 respondents. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS software version 22, accompanied by validity, reliability, and classical assumption tests. The results of the study showed that partially Digital Marketing had a positive and significant effect on Consumer Buying Interest (β = 0.165; t = 2.053; Sig. = 0.043). Product Quality also has a positive and significant effect on Consumer Buying Interest (β = 0.167; t = 3.627; Sig. = 0.000). In addition, Brand Image had a positive and significant effect and became the most dominant variable (β = 0.312; t = 3.693; Sig. = 0.000). Simultaneously, Digital Marketing, Product Quality, and Brand Image have a significant effect on Consumer Buying Interest (F = 44.205; Sig. = 0.000). The value of the determination coefficient (Adjusted R²) of 0.577 indicates that 57.7% of the variation in Consumer Buying Interest can be explained by all three independent variables, while the rest is influenced by other factors outside the study. The results of this study confirm that the increase in consumer buying interest is not only influenced by product quality and brand image strength, but also supported by the implementation of an effective and targeted digital marketing strategy.